QARAQALPAQSTAN RESPUBLIKASÍ OYKONIMLERIN RAYONLASTÍRÍW MÁSELELERI - Baltabayev, O.O. (ILIM hám JÁMIYET, 2025)
In this article, the definition and cartographic developments given by foreign and local scientists on toponymic region and zoning issues were studied. For the first time, the author conducted the zoning of the oikonyms of the Republic of Karakalpakstan and developed a map of oikonymic zoning.